구강 사마귀모양 황색종의 임상 및 병리조직학적 특성 - 고다은; 윤정훈; Da-Eun Ko; Jung-Hoon Yoon (대한구강악안면병리학회지, 2024)
Oral verruciform xanthoma (OVX) is an uncommon benign lesion of the oral mucosa, clinically mimicking various verrucous lesions. This study aimed to describe the clinicopathological characteristics of OVX. Twenty-one patients diagnosed with OVX were collected. The patients’ age, sex, medical history, clinical features, and treatment were reviewed. Archived slides were reviewed, and periodic acid-Schiff (PAS) and immunohistochemical (IHC) staining with CD68, CD1a, and S-100 were performed. OVXs affected 13 males and 8 females (M: F=1.6:1) with a mean age of 52 ± 21 years. The most prevalent site was the gingiva (57.1%), followed by the hard palate (28.5%). The lesions presented as an asymptomatic solitary lesion with verrucous or granular surface, with exception of one case with multiple papules on the hard palate. PAS-positive granules were found in xanthoma cells in 14 (66%) specimens. IHC revealed that xanthoma cells were positive for CD68 and negative for CD1a and S-100 in all specimens. Most lesions were successfully excised, and none of the lesions have recurred. Clinicians should include OVX in the differential diagnosis of various verrucous lesions in the oral cavity to provide appropriate management.